Bubble chemical effect and its influence on properties of sea water - Kushnir, S.V.; Kozak, R.P.; Kost’, M.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
It is shown that the transmission passive gases causes the bubble chemical effect (BCE), which is reduced to strong changes in pH (1–3 units) independent of the variables Eh. The reason for these changes is the intensive formation of a new gas/water surface, which is acidic in nature and provides the formation of an acid aerosol with positive charge. If the strong outflow of an aerosol due to the charge separation, pH of the solution is increasing and can reach the alkaline level (pH ∼8), which is the alkaline BCE; with a weak removal, pH of a solution is reduced, and the acidic BCE arises. The alkaine BCE was be able to play an important role in supporting the alkaline nature of ocean water throughout the Phanerozoic.